Do long‐term swap rate and stock price give an impact on Japanese Real Estate Investment Trust market under quantitative and qualitative easing and negative interest rate policy?. Issue 3 (29th November 2019) - Ito, Takayasu
Abstract: An increase in stock price has a positive impact on the Real Estate Investment Trust (REIT) market, but an increase in interest rate has a negative impact on the REIT market in the regime of quantitative and qualitative easing (QQE). The wealth effect holds. As for the impact of interest rate, swap rate of 30 years is larger than that of 20 years in the period of QQE. On the other hand, all the negative coefficients of stock price are statistically significant at the 1% level in the period of negative interest rate policy (NIRP). But none of the negative coefficients of interest rate are significant even at the 10% level. This result is very rare in the analysis of REIT market not only in Japan, but also in other countries such as USA. Investors tend to buy REITs to compensate for the sluggish stock market and reduced gains in the fixed income market. When the Bank of Japan adopts QQE, normal function of REIT market is maintained. But after they introduce NIRP, normal function of REIT market is lost. This phenomenon is a negative effect of NIRP.